2001
DOI: 10.1097/00004694-200109000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: There are few clear guidelines on the proper use of tourniquets in pediatric surgery, in particular on how to set the tourniquet pressure, how to select the most appropriate cuff, and whether to use some type of soft padding beneath the cuff for limb protection. The authors could find only one published study specifically addressing pediatric cuff pressures, and no studies showing what types of cuff and/or padding create the smoothest skin surface under the cuff. Of 46 pediatric orthopaedic surgeons surveyed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…As authors mention, this topic has not been studied largely and many of the published articles were case reports. Not many studies have been performed on tourniquet use in children ( 91 - 93 ) (to the best of our knowledge). In fact, the principles are not much different from adults.…”
Section: Resultsmentioning
confidence: 99%
“…As authors mention, this topic has not been studied largely and many of the published articles were case reports. Not many studies have been performed on tourniquet use in children ( 91 - 93 ) (to the best of our knowledge). In fact, the principles are not much different from adults.…”
Section: Resultsmentioning
confidence: 99%
“…If LOP is <130 mm Hg, the safety margin is 40 mm Hg; for LOP 131–190 mm Hg, the margin is 60 mm Hg; and if LOP is >190 mm Hg, the margin is 80 mm Hg 37. For pediatric patients, adding 50 mm Hg has been recommended 38. Studies have shown that cuff pressure based on LOP measured immediately prior to surgery is generally lower than the commonly used cuff pressures and is sufficient to maintain a satisfactory surgical field 39.…”
Section: Search Strategymentioning
confidence: 99%
“…A protocol based on measuring limb occlusion pressures (LOP), even among children, would be ideal but this practice has not been widely adopted 5. While the tourniquet time (112 min) used for our patient was within widely accepted safe limits, the inflation pressure (250 mmHg) may be too high considering his baseline SBP of 100–120 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no clear or widely accepted guidelines on the use of tourniquet in both adult and pediatric settings 1, 3, 5. Most authors agree that limiting the tourniquet time to 2 h is considered ideal 1, 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation